Risk factors for human immunodeficiency virus infection among Brazilian blood donors: a multicentre case–control study using audio computer‐assisted structured interviews. Issue 2 (20th March 2013) - de Almeida‐Neto, C.; Goncalez, T. T.; Birch, R. J.; de Carvalho, S. M. F.; Capuani, L.; Leão, S. C.; Miranda, C.; Rocha, P. C.; Carneiro‐Proietti, A. B.; Johnson, B. R.; Wright, D. J.; Murphy, E. L.; et al.
<x xml:space="preserve">Abstract</x> Background Although risk factors for HIV infection are known, it is important for blood centres to understand local epidemiology and disease transmission patterns. Current risk factors for HIV infection in blood donors in Brazil were assessed. Methods A case–control study was conducted at large public blood centres located in four major cities between April 2009 and March 2011. Cases were persons whose donations were confirmed positive by enzyme immunoassays followed by Western blot confirmation. Audio computer‐assisted structured interviews (ACASI) were completed by all cases and controls. Multivariable logistic regression was used to estimate adjusted odds ratios (AORs) and associated 95% confidence intervals (CIs). Results There were 341 cases, including 47 with recently acquired infection, and 791 controls. Disclosed risk factors for both females and males were sex with an HIV‐positive person AOR 11·3, 95% CI (4·1, 31·7) and being an IVDU or sexual partner of an IVDU [AOR 4·65 (1·8, 11·7)]. For female blood donors, additional risk factors were having male sex partners who also are MSM [AOR 13·5 (3·1, 59·8)] and having unprotected sex with multiple sexual partners [AOR 5·19 (2·1, 12·9)]. The primary risk factor for male blood donors was MSM activity [AOR 21·6 (8·8, 52·9)]. Behaviours associated with recently acquired HIV were being a MSM or sex partner of MSM [13·82, (4·7, 40·3)] and IVDU [11·47, (3·0, 43·2)]. Conclusion Risk factors in blood donors parallel those in the general population in Brazil. Identified risk factors suggest that donor compliance with selection procedures at the participating blood centres is inadequate.